Does training respiratory physicians in clinical respiratory physiology and interpretation of pulmonary function tests improve core knowledge?. Issue 1 (3rd March 2017) - Patout, M; Sesé, L; Gille, T; Coiffard, B; Korzeniewski, S; Lhuillier, E; Pradel, A; Tardif, C; Chambellan, A; Straus, C; Matecki, S; Perez, T; et al.
Abstract : Lung function tests have a major role in respiratory medicine. Training in lung function tests is variable within the European Union. In this study, we have shown that an internship in a lung function tests laboratory significantly improved the technical and diagnostic skills of French respiratory trainees.